Flavors of Ecstasy: States of Absorption in Islamic and Jewish Contemplative Traditions - Fisher, Nathan E. (2022)
While the trait of absorption has received a considerable amount of scientific study, states of absorption have been comparatively understudied and even less scholarly or scientific attention has been paid to those that are cultivated within the contemplative traditions of Islam and Judaism. This paper explores canonical descriptions of states of contemplative absorption in Islamic and Jewish traditions, specifically highlighting how they are often cultivated using sensory deprivation and sensory withdrawal, can be distressing and entail functional impairment considered normative in some contexts, and how some are set apart as the goal of specific meditative paths. The import of this survey goes beyond just historical significance, since these traditions assume, and recent research suggests it is plausible, that such states may be hyper-plastic and pivotal in both adaptive and maladaptive directions.
Keywords: Kabbalah; Sufism; perceptual decoupling; Abrahamic contemplative traditions; Ecstasy; Absorption